Peningkatan Kapasitas Pengelola Badan Usaha Milik Desa dalam Pengelolaan Keuangan: Studi Pada BUMNAg di Sumatera Barat - Rita Rahayu; Husna Roza; Sri Dewi Edmawati; Abdul Karib (Jurnal Pemberdayaan Ekonomi, 2022)
Purpose: The activity aims to improve the ability of BUMDes managers in terms of financial management. The reason for this activity is that the understanding and ability of BUMDes managers, especially in West Sumatra, is still low regarding financial management. Method: The method used in this activity is to carry out ongoing training and mentoring programs, which are carried out for a period of 6 months. Result: It is hoped that the activities carried out in a sustainable manner will certainly increase the ability and understanding of BUMDes managers, especially those in West Sumatra in terms of financial management. One of the outputs of this activity is that BUMDes are able to prepare their financial reports. Conclusion: This training and mentoring activity is very useful, especially with the issuance of PP No. 11 of 2021 concerning BUMDEs, one of which is to require BUMDes to compile accountability reports in the form of periodic financial reports. Contribution: This activity will certainly contribute in terms of developing the capacity of human resources in the village, and will certainly have a positive impact on improving the village economy.